Pyrrolinone derivatives as a new class of P2X3 receptor antagonists. Part 3: Structure-activity relationships of pyrropyrazolone derivatives. Issue 24 (15th December 2020) - Tobinaga, Hiroyuki; Kameyama, Takayuki; Asahi, Kentarou; Horiguchi, Tohru; Oohara, Miho; Taoda, Yoshiyuki; Hata, Kayoko; Hasegawa, Tsuyoshi; Tada, Yukio; Kurihara, Naoko; Kanda, Yasuhiko; Yagi, Shigenori; et al.
Graphical abstract: Highlights: Pyrropyrazolone derivatives as a P2X3 receptor antagonist were synthesized. The SAR studies were started from hit compound 3 with reference to the previous reported SAR studies from hit compound 1 . Orally bioavailable compound ( S )-42 was discovered. Compound ( S )-42 showed the analgesic effect almost same as pregabalin by increasing the dosage. Abstract: The P2X3 receptor is an attractive target for the treatment of pain and chronic coughing, and thus P2X3 antagonists have been developed as new therapeutic drugs. We previously reported selective P2X3 receptor antagonists by derivatization of hit compound 1 . As a result, we identified hit compound 3, the structure of which was similar to hit compound 1 . On the basis of SAR studies of hit compound 1, we modified hit compound 3 and compound 42 was identified as having analgesic efficacy by oral administration.